(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article examines modern approaches to personnel management in organizations. An analysis of existing personnel management methods is carried out, including selection, adaptation, training and motivation of employees. Key problems are considered and recommendations for improving the personnel management system are proposed, including the introduction of a balanced KPI system.